Mouse tales - Lobel, Arnold; Lobel, Arnold (Surrey : World's Work Ltd., 1977)
Papa Mouse has a funny, exciting bedtime story for each of his seven mouse boys.'Will evoke chuckles of glee from preschool listeners and beginning readers'.-Booklist. Three-color illustrations. Seven mouse boys lie awake one night, and they ask their Papa to tell them a story. Papa does better than that-he tells them seven stories, one for each boy. Amusing drawings and text provide beginner readers with a collection of tales about the adventures of mice.
The wishing well -- Clouds -- Very tall mouse and very short mouse -- The mouse and the winds -- Journey -- The old mouse -- The bath.
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Mice -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Storytelling -- Juvenile fiction; Wit and humor, Juvenile; Children's stories